Public enterprises in Spain: historical cycles and privatizations - Comín, Francisco (2008)
This paper presents an historical account of the public enterprise in Spain, focusing on the recovery of public enterprise in the 20th century, its consolidation following the Second World War and the large-scale privatizations in the last decade of the century. It shows that Spanish public business sector was among the smallest in Europe. At the same time, the public sector in Spain was very much manufacturinginclined due to the frailty of its public financial enterprises. For that reason, the scale of privatization was smaller in Spain than in the rest of Europe. However, Spain’s privatizations were carried out more efficiently and more rapidly than in other European Union countries. Finally, the paper shows that in Spain the privatized companies preserved their command of the market.